The Impact of Unconventional Monetary Policy Measures by the Systemic Four on Global Liquidity and Monetary Conditions - Korniyenko, Yevgeniya (IMF Working Papers; Working Paper, 2015)
The paper examines the impact of unconventional monetary policy measures (UMPMs) implemented since 2008 in the United States, the United Kingdom, Euro area and Japan- the Systemic Four-on global monetary and liquidity conditions. Overall, the results show positive significant relationships. However, there are differences in the impact of the UMPMs of individual S4 countries on these conditions in other countries. UMPMs of the Bank of Japan have positive association with global liquidity but negative association with securities issuance. The quantitative easing (QE) of the Bank of England has the opposite association. Results for the quantitative easing measures of the United States Federal Reserve System (U.S. Fed) and the ECB UMPMs are more mixed.